Anisotropic flow of identified particles in Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Klewin, Sebastian; Leardini, Lucia; et al. (Journal of high energy physics, 2018)
The elliptic (v2), triangular (v3), and quadrangular (v4) flow coefficients of π±, K±, p+p¯¯¯,Λ+Λ¯¯¯¯,K0Sp+p¯,Λ+Λ¯,KS0 p+\overline{p},\kern0.5em Λ +\overline{Λ},\kern0.5em K_{S}^0 , and the ϕ-meson are measured in Pb-Pb collisions at s√NN=5.02sNN=5.02 {\sqrt{s}}_{NN}=5.02 TeV. Results obtained with the scalar product method are reported for the rapidity range |y| < 0.5 as a function of transverse momentum, pT, at different collision centrality intervals between 0-70%, including ultra-central (0-1%) collisions for π±, K±, and p+p¯¯¯p+p¯ p+\overline{p} . For pT < 3 GeV/c, the flow coefficients exhibit a particle mass dependence. At intermediate transverse momenta (3 < pT < 8-10 GeV/c), particles show an approximate grouping according to their type (i.e., mesons and baryons). The ϕ-meson v2, which tests both particle mass dependence and type scaling, follows p+p¯¯¯p+p¯ p+\overline{p} v2 at low pT and π± v2 at intermediate pT. The evolution of the shape of vn(pT) as a function of centrality and harmonic number n is studied for the various particle species. Flow coefficients of π±, K±, and p+p¯¯¯p+p¯ p+\overline{p} for pT < 3 GeV/c are compared to iEBE-VISHNU and MUSIC hydrodynamical calculations coupled to a hadronic cascade model (UrQMD). The iEBE-VISHNU calculations describe the results fairly well for pT < 2.5 GeV/c, while MUSIC calculations reproduce the measurements for pT < 1 GeV/c. A comparison to vn coefficients measured in Pb-Pb collisions at sNN−−−√=2.76sNN=2.76 \sqrt{s_{NN}}=2.76 TeV is also provided. Open image in new window
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, M.K. Köhler, S. Klewin, L. Leardini, J. Mercado Pérez, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und weitere]
Gesehen am 21.06.2019